The rs3768777-G allele of ITGAV gene is associated with rheumatoid arthritis - Koca, Suleyman Serdar; Kara, Murat; Ozgen, Metin; Dagli, Mustafa Necati; Gozel, Nevzat; Yolbas, Servet; Isik, Ahmet (Springer Heidelberg, 2014)
Integrin alpha v beta 3 (vitronectin receptor) plays a prominent role in angiogenesis, a key pathogenic feature of rheumatoid arthritis (RA). Moreover, integrin alpha(V) (ITGAV) subunit gene has been associated with a susceptibility to RA. The aim of the present study was to detect the potential association between ITGAV gene polymorphisms and a susceptibility to RA in a Turkish cohort. DNA samples were harvested from 160 patients with RA and 144 healthy controls (HC). Three single-nucleotide polymorphisms of ITGAV gene (rs3738919, rs3768777, and rs10174098) were genotyped using real-time PCR. Serum vitronectin levels were analyzed in 30 RA patients, 28 Beh double dagger et's disease (BD) patients, and 30 HC subjects. There was no significant difference between the RA and HC groups in terms of the genotypic and allelic distributions of rs3738919 and rs10174098 polymorphisms. However, the prevalence of rs3768777-G allele was higher in the RA group than in the HC group (OR 2.3, 95 % CI 1.6-3.2, p < 0.0001). Moreover, there was a significant association between RA and the genotypic distribution of rs3768777 (GG + AG vs. AA: OR 2.1, 95 % CI 1.3-3.4; GG vs. AG + AA: OR 4.1, 95 % CI 2.1-7.8). Serum vitronectin levels were lower in the RA and BD groups than in the HC group (p (ANOVA) = 0.002). The rs3738919 and rs10174098 polymorphisms of the ITGAV gene seem not to be associated with susceptibility to RA in Turkish patients. However, rs3768777 increases the risk of RA in this group. These results suggest that the ITGAV gene may be a candidate gene for the etiopathogenesis of RA.
Keywords: Rheumatoid arthritis; Vitronectin; ITGAV gene